Clinical Outcomes of Unrelated Umbilical Cord Blood Graft vs. Haploidentical Donor Transplantation: Critical Issues for an Adequate Comparison - Vanegas, Diana; Niño-Quiroga, Laura; Chaparro, Mauricio; Camacho-Rodríguez, Bernardo; Estupiñán, Marcela; Perdomo-Arciniegas, Ana-María (Frontiers in Medicine, 2021)
Unrelated umbilical cord blood (UCB) and haploidentical grafts have been used for allogeneic hematopoietic stem and progenitor cell (HSPC) transplantation in patients without a related or non-related human leukocyte antigen (HLA)-matched donor. The less stringent HLA-matching requirement in both sources raises an important possibility for patients in need of urgent transplantation to treat any hematological disease. Selection of the best alternative donor is a difficult task that will depend on donor criteria, center experience, patient disease conditions, and risk, among others. Most comparisons available in scientific publications between both graft sources are obtained from retrospective analysis in wide time windows and a heterogeneous number of patients, types of disease, disease stages, previous treatments, graft source, conditioning regimen, graft vs. host disease (GVHD) approach, and evaluable endpoints. There is also an evident impact of the economic traits since low-income countries must consider less expensive treatments to satisfy the needs of the patients in the most effective possible path. Therefore, haploidentical transplantation could be an appealing option, even though it has not been completely established if any chronic treatment derived from the procedure could become a higher cost. In Colombia, there is a huge experience in UCB transplantation especially in units of pediatric transplantation where benign indications are more common than in adults. Due to the availability of a public UCB bank and HLA high-resolution typing in Colombia, there is a wider inventory of cord blood donors. Unfortunately, we do not have an unrelated bone marrow donor registry, so UCB is an important source along with haploidentical transplantation to consider in decision-making. This minireview focuses on comparing the main issues associated with the use of both HSCP sources and provides tools for physicians who face the difficult decision between these alternative donor sources.